Co-designing in the real world: managing a multiple stakeholder design process with an NGO - Brittan Sarah (Department of Computer Science, 2019)
Many ICT4D research projects work in collaboration with NGOs in order to meet their development objectives and to increase their interventions’ effectiveness. Herein, aspects of co-design are often applied, where the intention is to include all stakeholders as equal participants in the design process. However, collaborating with NGOs and with users who have reduced access to technology can be challenging. As a result, the ideals of co-design are not easily achieved, due to the vastly differing backgrounds of stakeholders in ICT4D projects. In this thesis, an explicit approach for managing the varying interactions between stakeholders is proposed and described through a case study. The approach was derived from ethnographic action research and participatory design methodologies, led by practical consideration from real-world constraints. The approach is structured around an interactive design process that includes the stakeholder groups in unique ways at each phase of the design process, in order to maximise the contributions in a way that respects their backgrounds and areas of expertise. The proposed approach was evaluated through its implementation in the design of a mobile recordkeeping application, in collaboration with an NGO in Cape Town, South Africa. The NGO comprises of two stakeholder groups: the staff and the micro-entrepreneurs who they empower. The NGO’s focus is to provide training and support over a two-year process to women from low-income communities, by teaching them how to manage their own businesses to become socially and financially independent. The objective of this case study was to design a mobile application that aligned with the recordkeeping curriculum of the NGO and meet the specific requirements and constraints of the target users. Through the implementation of the design approach, the students and staff were able to provide useful and complementary contributions towards the design of the system. A one-month field study of the application with a group of 21 student participants revealed that the system was a suitable solution and appropriately met the needs of the NGO and the end-users. The final evaluation of the stakeholders’ reflections on the design process revealed that it was an appropriate design process to have followed. The results further identified that care must be taken to clarify expectations at each stage of the design process, especially when external factors change, and to frequently communicate with all stakeholders involved. The design approach proposed and employed during this research project, and the unique way that it allowed the stakeholders to contribute, will benefit future ICT4D research projects that are faced with stakeholder groups that vary significantly, where traditional equal participation is not possible.